2017
DOI: 10.1002/jssc.201700076
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐imprinted microspheres prepared by a template‐oriented method for the chiral separation of amlodipine

Abstract: The surface imprinting technique has been developed to overcome the mass-transfer difficulty, but the utilization ratio of template molecules in the imprinting procedure still remains a challengeable task to be improved. In this work, specifically designed surface-imprinted microspheres were prepared by a template-oriented method for enantioseparation of amlodipine besylate. Submicron mesoporous silica microspheres were surface-modified with double bonds, followed by polymerizing methacrylic acid to generate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…In the second stage, the weight of PSMIPs, SMIPT, and Mal‐β‐CD reduced to approximately 50, 30, and 15% of the original weight, respectively. The different weight loss of PSMIPs and SMIPT could be attributed to Mal‐β‐CD imprinted into the surface of functionalized silica particles . Similar results were obtained by Gong et al.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In the second stage, the weight of PSMIPs, SMIPT, and Mal‐β‐CD reduced to approximately 50, 30, and 15% of the original weight, respectively. The different weight loss of PSMIPs and SMIPT could be attributed to Mal‐β‐CD imprinted into the surface of functionalized silica particles . Similar results were obtained by Gong et al.…”
Section: Resultssupporting
confidence: 85%
“…In the second stage, the weight of PSMIPs, SMIPT, and Mal-β-CD reduced to approximately 50, 30, and 15% of the original weight, respectively. The different weight loss of PSMIPs and SMIPT could be attributed to Mal-β-CD imprinted into the surface of functionalized silica particles [29]. Similar results were obtained by Gong et al [21], who reported that the weight loss of PSMIPs between 300 and 650 • C was caused by the removal of organic compounds in the surface imprinted layer.…”
Section: Stability and Reusability Of Psmipssupporting
confidence: 78%
“…Recently, Lai et al . synthesized chiral imprinted microspheres that showed 11.3 % enantiomeric excess (ee) and surface‐imprinted microspheres provided 13.8% ee of the drug (S)‐amlodipine . Another example of chiral separation is enantioselective crystallization on the surface of chiral polymeric microspheres, based on polystyrene, which led to as much as 25 % ee enrichment of L‐valine .…”
Section: The Results Of Optical Rotation and CD Measurementsa At 25 °mentioning
confidence: 99%
“…Functional polymeric microspheres, which are often used in chemical catalysis and adsorption, have some special advantages, including a large specific surface area, strong adsorption capacity, surface reaction ability, and ease of modification [1,2], tumor embolization [3,4], information transfer [5], chromatographic separation [6], and biomedicine [7]. Transcatheter arterial embolization (TAE) was first reported by Yamamoto et al [8] in 1991, which was an effective technique for the insertion of a catheter into a target tissue or organ.…”
Section: Introductionmentioning
confidence: 99%